2010
DOI: 10.1111/j.1365-2915.2010.00887.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure and population dynamics of the biting midgesCulicoides obsoletusandCulicoides scoticus: implications for the transmission and maintenance of bluetongue

Abstract: Abstract. Culicoides species belonging to the Obsoletus complex (Diptera: Ceratopogonidae) have been indicated as primary bluetongue (BT) vectors in many European countries and their possible involvement in the maintenance and overwintering of BT viruses has been suggested, even in regions where Culicoides imicola Keiffer is the main vector. The Obsoletus complex includes two predominant taxa, Culicoides obsoletus (Meigen) and Culicoides scoticus Downes & Kettle. However, the role played by each species in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Physiological status CDC (CO 2 and (R)-1-octen-3-ol) a The evidence for involvement of members of the Avaritia subgenus in BTV transmission in both southern and northern Europe is far stronger than that for C. nubeculosus, although our understanding of the role of individual species within this group during epizootics remains limited , Pili et al 2010. As expected, numbers of Culicoides collected directly from a live host substantially exceeded those collected using semiochemical traps indicating the fact that host location involves multiple and complex visual, thermal and olfactory stimuli, which are difÞ-cult to replicate artiÞcially (Logan and Birkett 2007).…”
Section: Speciesmentioning
confidence: 99%
“…Physiological status CDC (CO 2 and (R)-1-octen-3-ol) a The evidence for involvement of members of the Avaritia subgenus in BTV transmission in both southern and northern Europe is far stronger than that for C. nubeculosus, although our understanding of the role of individual species within this group during epizootics remains limited , Pili et al 2010. As expected, numbers of Culicoides collected directly from a live host substantially exceeded those collected using semiochemical traps indicating the fact that host location involves multiple and complex visual, thermal and olfactory stimuli, which are difÞ-cult to replicate artiÞcially (Logan and Birkett 2007).…”
Section: Speciesmentioning
confidence: 99%
“…In Sardinia, populations of C. imicola appeared only from April to December, meanwhile C. obsoletus, C. newsteadi and C. pulicaris were captured all year around (Foxi and Delrio, 2010;Foxi et al, 2011). Pili et al (2010) confirmed that C. scoticus was most abundant from late winter to early spring, whereas C. obsoletus was prevalent in early summer. A similar pattern was also found in Corsica (Venail et al 2012).…”
Section: South Europementioning
confidence: 71%
“…Pili et al. () confirmed that C. scoticus was most abundant from late winter to early spring, whereas C. obsoletus was prevalent in early summer. A similar pattern was also found in Corsica (Venail et al.…”
Section: Assessmentmentioning
confidence: 94%
“…Three principal routes of virus introduction into Europe have been identified, all of them situated in areas where multiple vector species occur (Calvete et al, 2008;Pili et al, 2010). At a distance, Europe would seem to consist of two BT sub-episystems: southern, with C. imicola, and northern, without C. imicola ).…”
Section: Possible Sub-episystems In Europementioning
confidence: 99%
“…The existence of zones with a higher risk of virus introduction is, however, recognised. Three principal routes of virus introduction into Europe have been identified, all of them situated in areas where multiple vector species occur (Calvete et al, 2008;Pili et al, 2010). These routes are: i) Morocco -Spain, ii) North-Africa -Western and Central Mediterranean islands and Italy, iii) Turkey -Greece (Wilson and Mellor, 2008).…”
Section: Possible Sub-episystems In Europementioning
confidence: 99%